For the function
We can use the formula for the axis of symetry, which is
With the values substituted, we get...
Therefore the axis of symmetry is
Answer:
x = -1 y = -1
Step-by-step explanation:
x + 3y = −4
x + 5y = −6
Multiply the first equation by -1
-x - 3y = 4
The add to the second equation to eliminate x
-x - 3y = 4
x + 5y = −6
--------------------
2y = -2
Divide by 2
2y/2 = -2/2
y = -1
Now solve for x
x+3y = -4
x +3(-1) = -4
x -3 = -4
Add 3 to each side
x-3+3 = -4+3
x = -1
Da answer is cCbecause it is